STRUKTUR MODAL: INFLASI, NON-DEBT TAX SHIELD, DAN AGRESIVITAS PAJAK - Septiananda, Nafillia; Pratiwi, Adhitya Putri (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya, 2023)
The purpose of this study is to identify and provide empirical evidence of the effect of inflation, non-debt tax shield and tax aggressiveness on capital structure. This study uses a sample of Basic Materials Companies Listed on the Indonesia Stock Exchange in 2017-2021. The data used in this study are financial reports and annual reports. The sampling technique used was purposive sampling, from 98 Basic Materials companies a sample of 14 companies was obtained for 5 years. The analysis used is panel data regression analysis using the Random Effect regression model. the data is processed with the help of Eviews 9 software. The results obtained show that simultaneously inflation, non-debt tax shield and tax aggressiveness have an effect on capital structure. The results obtained partially show that inflation has an effect on capital structure, non-debt tax shield has no effect on capital structure, and tax aggressiveness has no effect on capital structure.